Estado, luta de classes e políticas públicas de educação para o campo no Tocantins: territórios em disputa - Reis, Cleivane Peres dos (2015)
This thesis analyzes basic education policies to the camp in the State of Tocantins, implemented especially from 1990. Situated in the context of educational reforms oriented by international agencies committed to the capitalist mode of production - in order to forge an education adequate for the ideological domination and meet the demands of the labor market - the educational policy aimed at the working class in the camp is analyzed from a critical reading about state and public policies in the context of capitalism and of its cyclical crises. It´s evident in these paper the role of the state in the capital of the expansion process in the camp, as well as its consequences for the working class, which are expressed on the one hand, in the advance of agribusiness, and, second, in precarious conditions labor and return productive relationships already considered extirpated in society as slave labor in its contemporary setting. In the analysis carried out are taken as specific references so-called Citizenship Territories - elements of the contemporary process of territorialization of public policies for the camp - to allow the reflections on education policies for the camp in Tocantins. The focus is also the analysis of the theoretical production drawn up by the "Movement for a Rural Education," highlighting the contradictions present in such proposals, its limits, scope and possibilities. The simultaneous recurrence of Marxist Theory and the adoption of dialectical historical materialism, let along the paper to undertake the critical forms of support of capitalist society, while seeking the chances of your passing. In this sense, the reflections developed along this thesis depart from the principle of education is not an isolated one, that one understands neither be explained by itself. The analysis of its possibilities, limits, quality and extent, cannot therefore dispense with consideration of the material basis of society, of its organization and operation of its contradictions and present her class antagonisms. The final considerations will assert a lack of education policies to the camp in Tocantins, that would, in fact, the interests of the working class in the camp, and affirm the importance of the dialectic of the immediate components in theoretical and practical concepts of current educational policies for the camp, so that is enhanced manufacturing dimension of school education practices from the perspective of human emancipation and overcoming class society.